The Effects of Food Taxes and Subsidies on Promoting Healthier Diets in Iranian Households - Mokari-Yamchi, Amin; Omidvar, Nasrin; Tahamipour Zarandi, Morteza; Eini-Zinab, Hassan (Frontiers in Nutrition, 2022)
Background & aim: Price, as a key driver of food purchasing has an important role in determining the consumer demand. This study aims to estimate the effect of food taxes and subsidies on purchasing patterns of Iranian households (HHs). Methods: This study was performed in two phases. In Phase one, a two-round Delphi study was conducted to determine and prioritize food-related fiscal policies; and in the second phase, using the Iranian Household Income & Expenditure Survey (HIES), we estimated an almost ideal demand system (AIDS) and simulated changes in purchases, nutrient intake, and consumer welfare under six different policy scenarios: 1) 20% subsidy on vegetables, 2) 20% subsidy on fruits, 3) 30% subsidy on legumes, 4) 25% tax on sugar and sweets, 5) 30% tax on sweetened beverages, and 6) 30% tax on hydrogenated oil and animal fats. Results: The highest calorie reduction was detected in sugar and sweets tax which has resulted in 949.67, 971.68 and 1148.03 kilocalories decrease in energy intake per Adult Male Equivalent (AME) in all HHs, low income HHs, and high income HHs, respectively. In terms of welfare changes, high-income HHs will experience a lower change in welfare (-0.81% to 0.11%) relative to their income compared with low-income HHs (-0.88% to 0.28%) due to fiscal policies. Conclusion: Fiscal policies in Iran can be a potential way to improve dietary choices. The findings provide essential information for decision makers for implementation of food-related fiscal policies.